2015
DOI: 10.1097/mpa.0000000000000466
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Qualitative Magnetic Resonance Imaging Features for Diagnosis of Chronic Pancreatitis

Abstract: Qualitative MRI parenchymal and ductal features are associated with CP. Presence of 6 or more features results in a higher specificity for the diagnosis of CP in advanced disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Among the prior reports [22, 2430], the most comparable study correlating the T1-weighted signal intensity of the pancreas with pancreatic function test was by Balci et al [28]. In that study, there was no T1 signal difference between normal and low bicarbonate groups, pancreatic juice was sampled from the duodenal lumen, and there were only 12 patients in the decreased exocrine function group compared to 22 in our study.…”
Section: Discussionsupporting
confidence: 49%
“…Among the prior reports [22, 2430], the most comparable study correlating the T1-weighted signal intensity of the pancreas with pancreatic function test was by Balci et al [28]. In that study, there was no T1 signal difference between normal and low bicarbonate groups, pancreatic juice was sampled from the duodenal lumen, and there were only 12 patients in the decreased exocrine function group compared to 22 in our study.…”
Section: Discussionsupporting
confidence: 49%
“…Sensitivity and specificity of ECV fraction and T1 mapping were superior to T1-weighted SIR of pancreas to either spleen or paraspinal muscle, duodenal filling after secretin stimulation, and arteriovenous enhancement ratio of the pancreas. Sensitivity and specificity were also higher than in published studies that examined qualitative imaging criteria of CP using multiple qualitative MRCP findings, DWI to detect pancreatic fibrosis, T1-weighted SIR of the pancreas to paraspinal muscle correlated with histopathology, and grading of duodenal filling to detect the decreased exocrine fluid volume of the pancreas [12, 19, 25, 27, 28]. Prior studies often reported difficulty in assessing the severity of CP.…”
Section: Discussionmentioning
confidence: 85%
“…44 Finally, MR cholangiopancreatography, in conjunction with stimulation of the pancreas by secretin, has been used to assay pancreatic secretory responses by quantitative assessment of fluid secreted into the gut lumen and for simultaneous assessment of duct morphology and compliance. 45 There is need for a quantitative scoring system as a biomarker for CP. Such a scoring system is the focus of the MINIMAP study (MRI as a noninvasive method for the assessment of pancreatic fibrosis), which is funded by NIDDK.…”
Section: Quantitative Imaging Of Cpmentioning
confidence: 99%